Candidatos a transplante hepático com doença hepática alcoólica: aspectos psicossociais. - Diogo Telles-Correia (Acta Médica Portuguesa, 2011)
One of the most common indications for Liver transplantation is Alcohol Liver Disease (ALD). Transplant recipients with ALD have a similar prognosis in terms of medical evolution and quality of life to those with other liver diseases. ALD is present when alcoholism (alcohol dependence /abuse) or heavy drinking coexists with chronic/acute liver disease. In the present article difficulties in establishing this diagnosis are debated. The main predictors of alcohol intake relapse after transplantation are: pre-transplantation abstinence (> 6m), social support, diagnosis acceptance, history of previous treatments, alcohol abuse VS dependence, Vaillant prognosis factors, good adherence (good prognosis); and family history of alcoholism, psychiatric history (psychosis, personality disorder), duration of alcoholism period, quantity of alcohol /day consumed (bad prognosis). Based in these factors we present a new evaluation scale. Diagnosis of alcohol relapse depends on the criterion used. Relapse rate is 5.6% /year. In the end of this article we discuss the different psychopharmacological and psychological methods used to treat pos-transplantation alcoholism relapse and some ethical aspects related to discrimination of patients with ALD.